Pemanfaatan Linguistik dalam Media Pembelajaran Digital - Nor Fajriatul Khasanah; Ulfi Khulaya; Olivia Maria Ulfah (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study analyzes the utilization of linguistics in digital learning media and its role in improving the effectiveness of instructional content delivery. The rapid advancement of educational technology has increased the use of digital platforms in learning, yet language use in these media is often ineffective and unsuitable for learners’ levels of understanding. This research employs a qualitative descriptive case study approach, with data collected through a systematic literature review of journals, books, and examples of digital learning media. The findings indicate that linguistic aspects, particularly syntax, semantics, and pragmatics, play a significant role in creating instructional materials that are clear, understandable, and engaging. The study also reveals that limited teacher competence in applied linguistics remains a major challenge in integrating linguistic principles into digital learning environments. Effective implementation requires communicative learning activities, systematic linguistic feedback, and the support of digital tools such as grammar-checking applications and language-learning platforms. The study concludes that integrating linguistic principles can enhance learning quality and student outcomes significantly.